Relationship between burnout and nicotine dependence levels of health care assistants in a university hospital sample - Beşe, Tuba; Mıhcı, Özge; Ayhan Başer, Duygu; Cankurtaran, Mustafa (Journal of Dependence, 2020)
Objective: The aim of this study was to determine the smoking status and the burnout levels of health care assistants, to examine the relationship between burnout level and smoking status, severity of nicotine addiction.Method: A descriptive epidemiological research was carried out on health care assistants working at the Medical Faculty Hospital. All health care assistants were tried to be reached without making a sample calculation. A questionnaire including Maslach Burnout Scale (MBS) and Nicotine Addiction Scale (NAS) was applied face-to-face.Results: 68.2% of the participants are women; 37.5% were between the ages of 36-45. 40.9% of them were smoking. A statistically significant difference was found only between the smoking status and the working year in the hospital. When the MBS sub-scores were compared by smoking status, there was no statistically significant difference between the groups. As NAS scores increased, depersonalization scores increased and there was a weakly positive relationship between scale scores.Conclusion: No significant relationship was found between burnout levels and smoking among health care assistants. However it seems that the more insensitive staff is more addicted to smoking.
Keywords: Addiction; burnout syndrome; healthcare workers; nicotine